Haba, Juan de la; Santamaría, Enrique y Yufra, Laura C. (2014). Parlem-ne: Intervenció socioantropològica i conflictes relacionats amb els llocs de culte - Solana Solana, Miguel (Documents d'Anàlisi Geogràfica, 2017)
Haba, Juan de la; Santamaría, Enrique y Yufra, Laura C. (2014) Parlem-ne: Intervenció socioantropològica i conflictes relacionats amb els llocs de culte Barcelona: Pol·len Edicions / Institut Català d’Antropologia, 148 p. ISBN 9788486469771